2019
DOI: 10.1007/s13762-019-02364-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biocrude oil production from self-settling and non-settling microalgae biomass produced in the Qatari desert environment

Abstract: The present study investigated the growth, harvesting, biocrude conversion, and recycling of the HTL aqueous phase for one self-settling (i.e., Chlorocystis sp.) and another non-settling (i.e., Picochlorum sp.) marine microalgae. Both the strains were grown simultaneously in 2 identical 25,000-L raceway ponds in the Qatari desert. The cell size of Picochlorum sp. was small (2-3 µm), and its biomass was harvested using a centrifuge. Cells of Chlorocystis sp. (6-9 µm) formed flocs that settled spontaneously in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…were extensively grown in the Qatari desert environment. 51,52 The biomass densities found in outdoor 25000 L raceway ponds (Figure 1c,d) for all three strains were lower than those found in 1 L indoor PBRs. Among the three strains selected for outdoor cultivation, Coelastrella sp.…”
Section: Coefficient Of Friction (Cof) Analysis By a Pin-on-disk Trib...mentioning
confidence: 84%
“…were extensively grown in the Qatari desert environment. 51,52 The biomass densities found in outdoor 25000 L raceway ponds (Figure 1c,d) for all three strains were lower than those found in 1 L indoor PBRs. Among the three strains selected for outdoor cultivation, Coelastrella sp.…”
Section: Coefficient Of Friction (Cof) Analysis By a Pin-on-disk Trib...mentioning
confidence: 84%
“…Hydrothermal liquefaction (HTL) is a promising technology that can convert a variety of biomass, including microalgae, into biocrude oil in the presence of heat and pressure where the moisture in the biomass act as a solvent [173,174]. Under optimized conditions, the HTL process could recover more than 80% of the calorific value of the microalgal biomass feedstock [175].…”
Section: Biocrude Oilmentioning
confidence: 99%
“…In a recent study, it was shown that Picochlorum sp. could efficiently utilize the nutrients in the aqueous phase-derived from the HTL of its biomass (Das et al, 2019b). Although the concentrations of nitrogen in both these cultures were the same, the aqueous phase liquid had dissolved organics; therefore, Picochlorum sp.…”
Section: Aqueous Phasementioning
confidence: 99%
“…Although the toxic wastewater could be treated using microalgae, the produced biomass could have some estrogenic effect and hence should not be used for human and animal consumption (Correa-Reyes et al, 2007;López-Pacheco et al, 2019b). Nonetheless, the produced microalgal biomass, by using APL nutrients, could be used as biofuel feedstock (Das et al, 2019b), biofertilizer (Das et al, 2018b), and feedstock for many other renewable chemicals (Foley et al, 2011).…”
Section: Aqueous Phasementioning
confidence: 99%
See 1 more Smart Citation